PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (studi pada perusahaan yang terdaftar di Indeks LQ 45 Bursa Efek Indonesia tahun 2008- 2011) - , MOHAMMAD EDO AZHARA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research intents to find the influence of company size, leverage, profitability, and dividend policy on corporate value. This will help the investor when looking for the best portfolio. In so doing, it has used secondary data. Its tools of analysis are linear multiple regression and multiple correlation. The research results seem to be convincing, that three out four hypotheses succeed to be proven. The influence of company size on corporate value fail to be validated. The causal relationship of the rest of variables â leverage, profitability, and dividend policy â toward corporate value are successfully to be confirmed. However, it should be understood that the research still has weakness. In other words, the research variables need to be studied deeper, at least its time series data â by adding the number of years to be included.